Blankets, heat, and why free energy has not illuminated the workings of the brain. (29th September 2022) - Spector, Donald; Graham, Daniel
Abstract: What can we hope to learn about brains from the free energy principle? In adopting the "primordial soup" physical model, Bruineberg et al. perpetuate the unsupported notion that the free-energy principle has a meaningful physical – and neuronal – interpretation. We examine how minimization of free energy arises in physical contexts, and what this can and cannot tell us about brains.